Two-body wear comparison of zirconia crown, gold crown, and enamel against zirconia. (July 2015) - Kwon, Min-Seok; Oh, Sang-Yeob; Cho, Sung-Am
Abstract: Problem statement: Full zirconia crowns have recently been used for dental restorations because of their mechanical properties. However, there is little information about their wear characteristics against enamel, gold, and full zirconia crowns. Purpose: The purpose of this study was to compare the wear rate of enamel, gold crowns, and zirconia crowns against zirconia blocks using an in vitro wear test. Materials and methods: Upper specimens were divided into three groups: 10 enamels (group 1), 10 gold crowns (group 2, Type III gold), and 10 zirconia crowns (group 3, Prettau ® Zirkon 9H, Zirkonzahn, Italy). Each of these specimens was wear tested against a zirconia block (40×30×3 mm 3 ) as a lower specimen (30 total zirconia blocks). Each specimen of the groups was abraded against the zirconia block for 600 cycles at 1 Hz with 15 mm front-to-back movement on an abrading machine. Moreover, the load applied during the abrading test was 50 N, and the test was performed in a normal saline emulsion for 10 min. Three-dimensional images were taken before and after the test, and the statistical analysis was performed using the Krushal–Wallis test and Mann–Whitney test ( p =0.05). Results: The mean volume loss of group 1 was 0.47 mm 3, while that of group 2 and group 3 was 0.01 mm 3 . Conclusion: The wear volume loss of enamels against zirconia was higher than that of gold and zirconia crowns. Moreover, according to this result, zirconia crowns are not recommended for heavy bruxers.